Právní aspekty aplikace střevního mikrobiomu - Špeciánová, Šárka (Vnitrni lekarstvi, 2021)
Application of intestinal microbiome (Fecal Microbiota Transplantation) is currently discussed treatment procedure which is the subject of professional interest not only when it comes to its medical aspects, but also its legal regulation. The aim of this article is to introduce a legal perspective on this subject matter and outline possible newly regulated areas. The subject matter is linked not only with the legislation contained in the Czech Civil Code in the section devoted to products having its origin in the human body, but also with other laws in the area of medical law. The position of regulatory authorities in the EU is also mentioned. It is apparent that EUs regulatory authorities leave this area for the legislation of individual EU member States.
Keywords: metabolic and immunological effects of action; pharmacological; Law on medical devices; legal regulation de lege ferenda; Civil Code; Law on medicines; Gastrointestinal Microbiome; Law on tissues and cells; microbiome; products arising in the human body; Humans; střevní mikroflóra; Fecal Microbiota Transplantation; fekální transplantace; Microbiome; fecal microbiota transplantation; lidé; Transplantation Law